A grid-shaped porous carbon nitride photocatalyst and its preparation method and application

By using melamine and pyridine-2,5-dicarboxylic acid to prepare grid-like porous carbon nitride photocatalysts, the problem of insufficient photocatalytic performance of traditional carbon nitride materials is solved, high-efficiency photocatalytic oxidation and bactericidal effects are achieved, and the effect of high-efficiency photocatalytic oxidation and bactericidal are reduced. Production cost, suitable for large-scale applications.

CN115970726BActive Publication Date: 2024-12-20YANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211571555.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2024-12-20
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

Traditional carbon nitride photocatalysts have low yields, limited light absorption range, poor photocatalytic performance, which is difficult to apply in large-scale production, and the preparation process is complex, which violates the concept of sustainable development.

Method used

Melamine and pyridine-2,5-dicarboxylic acid were used as raw materials to prepare grid-like porous carbon nitride photocatalysts through π-π stacking, hydrothermal reaction and heat condensation reaction, and their light absorption range and photocatalytic properties were optimized.

Benefits of technology

The photocatalytic oxidation capacity of carbon nitride photocatalysts is significantly improved, the photocatalytic reaction rate is increased, and the organic pollutant rhodamine B can be efficiently degraded and multidrug-resistant bacteria can be killed. The preparation process is low-cost and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115970726B_ABST
    Figure CN115970726B_ABST
Patent Text Reader

Abstract

The invention discloses a grid-like porous carbon nitride photocatalyst and a preparation method and application thereof, wherein the grid-like porous carbon nitride photocatalyst comprises melamine and pyridine-2,5-dicarboxylic acid as raw materials, and is prepared by a three-step method of π-π stacking, hydrothermal reaction and thermal polycondensation reaction. The grid-like porous carbon nitride photocatalyst of the present invention introduces a pyridine group into the heptazine unit of the traditional carbon nitride material, greatly improves the performance of the photocatalytic material, expands the light absorption range, reduces the photogenerated carrier recombination, and enhances the photocatalytic oxidation ability; the photocatalyst is provided with a grid-like porous structure by using the stirring, hydrothermal reaction and thermal polycondensation of the raw materials in the acetic acid solution, and greatly increases the photocatalytic active sites; it is used for photocatalytic degradation of organic pollutants and photocatalytic oxidation sterilization, and the degradation rate is 5.12 times that of the unmodified one, the sterilization efficiency reaches 99.9%, the yield reaches 56%-76%, and the raw materials are easy to obtain, which is suitable for commercial promotion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a grid-shaped porous carbon nitride photocatalyst and a preparation method and application thereof, belonging to the technical field of photocatalytic materials. Background Art

[0002] Photocatalytic reaction is a type of reaction that uses the photogenerated carriers of materials to carry out chemical transformation. Under light irradiation, the material transitions from a steady state to an excited state, and photogenerated electron-hole pairs are generated during the transition process. Photogenerated electron-hole pairs can be used to carry out various oxidation-reduction reactions. Depending on the main components in the photocatalytic process, it can be divided into photocatalytic oxidation reaction and photocatalytic reduction reaction. The photogenerated electrons and holes generated during the photocatalytic reaction recombine quickly. In order to improve the catalytic ability of the photocatalyst, the photocatalyst must have good light absorption ability and the ability to hinder the recombination of photogenerated electrons and holes.

[0003] Photocatalytic technology has a very wide range of applications, and there have been a lot of studies on the decomposition of water to produce hydrogen, the synthesis of ammonia from nitrogen at room temperature, the reduction of carbon dioxide, the decomposition of organic pollutants, and the catalytic elimination of harmful bacteria. Traditional photocatalysts usually contain metal elements, and usually have high preparation costs and complicated preparation processes, which are not conducive to large-scale production and also violate the concept of sustainable development. Carbon nitride photocatalysts are a low-cost metal-free photocatalyst with a simple preparation process, but they also have limitations such as poor light absorption and rapid recombination of photogenerated carriers. The photocatalytic performance of carbon nitride materials needs to be further improved. Summary of the invention

[0004] Purpose of the invention: In view of the problems of low yield, limited light absorption range and poor photocatalytic performance of traditional carbon nitride materials, the first purpose of the present invention is to provide a high-yield grid-like porous carbon nitride photocatalyst; the second purpose of the present invention is to provide a method for preparing the grid-like porous carbon nitride photocatalyst; the third purpose of the present invention is to provide the application of the grid-like porous carbon nitride photocatalyst in photocatalytic oxidation.

[0005] Technical solution: The present invention discloses a grid-shaped porous carbon nitride photocatalyst, which is prepared by using melamine and pyridine-2,5-dicarboxylic acid as raw materials, undergoing π-π stacking, and then undergoing a hydrothermal reaction and thermal polycondensation reaction.

[0006] Wherein, the mixing mass ratio of melamine to pyridine-2,5-dicarboxylic acid is 1-10:1.

[0007] Among them, the preferred mixing mass ratio of melamine to pyridine-2,5-dicarboxylic acid is 4:1.

[0008] If the mass ratio of melamine and pyridine-2,5-dicarboxylic acid system is lower than this ratio, the absorption range of the prepared carbon nitride material will be significantly reduced, the replacement effect of the pyridine unit is insufficient, the photocatalytic performance is reduced, and the oxidation ability is weakened; if the mass ratio of melamine and pyridine-2,5-dicarboxylic acid system is too high, the heptazine structure of carbon nitride is destroyed, causing the photocatalytic performance of the material to decay sharply. Among them, the π-π stacking is the interaction of the raw materials melamine and pyridine-2,5-dicarboxylic acid in acetic acid solution through non-covalent bonds.

[0009] The π-π stacking is a special type of reaction between raw materials with aromatic structures, which is an interaction between non-covalent bonds. The reaction can occur spontaneously in an acetic acid solution.

[0010] The method for preparing the grid-shaped porous carbon nitride photocatalyst of the present invention comprises the following steps:

[0011] (1) adding melamine and pyridine-2,5-dicarboxylic acid to an acetic acid solution, ultrasonicating, stirring and mixing, and obtaining a milky white colloid through π-π stacking;

[0012] (2) placing the milky white colloid in a reaction kettle and performing a hydrothermal reaction to obtain a reaction product;

[0013] (3) washing and drying the reaction product, placing it in a quartz tube furnace for thermal polycondensation reaction, and grinding it to obtain the target grid-like porous carbon nitride photocatalyst.

[0014] Wherein, in step (1), the concentration of the acetic acid solution is 10%.

[0015] Wherein, in step (1), the temperature of the ultrasonic and stirring mixing is both 50-60°C.

[0016] The preferred temperatures for ultrasonic and stirring mixing are both 60°C.

[0017] Wherein, in step (2), the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 18-24 h.

[0018] The preferred hydrothermal reaction temperature is 170°C-180°C, and the hydrothermal reaction time is 24h.

[0019] The temperature of the hydrothermal reaction is preferably 170°C-180°C. If it is lower than 160°C, the yield of the reaction product is low, the reaction result is incomplete, and there are more raw materials that do not participate in the reaction in the product, which affects the subsequent thermal polycondensation reaction. If the temperature of the hydrothermal reaction is higher than 200°C, the product will be partially damaged due to the high temperature structure, which affects the subsequent reaction and generates impurities.

[0020] Wherein, in step (3), the thermal polycondensation reaction is carried out in an air atmosphere throughout the entire process.

[0021] Wherein, in step (3), the temperature of the thermal polycondensation reaction is 490-530°C, and the time of the thermal polycondensation reaction is 4-6h.

[0022] The preferred temperature for the thermal polycondensation reaction is 500° C.-510° C., and the preferred time for the thermal polycondensation reaction is 6 hours.

[0023] The reaction temperature of the thermal polycondensation reaction is preferably 500°C-510°C. If it is lower than 490°C, the reaction will not proceed completely and some raw materials cannot be completely converted into carbon nitride materials. If the reaction temperature is higher than 530°C, the generated carbon nitride material will be partially destroyed and converted into ammonia gas that overflows the tubular furnace, affecting the yield of the final product.

[0024] Wherein, in step (3), the washing solution is anhydrous ethanol and deionized water, and the washing is performed three times respectively.

[0025] The drying temperature is 50-60°C and the drying time is more than 6 hours.

[0026] The present invention also includes the use of the grid-shaped porous carbon nitride photocatalyst in photocatalytic oxidation degradation of the organic pollutant Rhodamine B.

[0027] Among them, the organic pollutant is Rhodamine B, which belongs to the anthraquinone class and is a common cationic alkaline dye that is highly toxic and carcinogenic.

[0028] The present invention also includes the use of the grid-shaped porous carbon nitride photocatalyst in photocatalytic oxidation to kill bacteria.

[0029] Among them, the bacteria are multidrug-resistant Acinetobacter baumannii, which is one of the main pathogens of aquaculture and hospital infections and can cause bacteremia, pneumonia, endocarditis and skin infections.

[0030] When melamine and pyridine-2,5-dicarboxylic acid are dispersed in an acetic acid system, they can form a gel due to the π-π stacking effect of the two raw materials through ultrasound and vigorous stirring, and the subsequent hydrothermal reaction and thermal polycondensation reaction will be more sufficient. The reason for maintaining the condition of 50-60° C. during ultrasound and stirring is that the reaction rate is fast in a higher solution system, and the white colloid formed by π-π stacking after the reaction is terminated is more compact.

[0031] The carbon nitride photocatalyst prepared entirely from melamine is composed of a combination of heptazine structures, but due to the low specific surface area, inefficient light absorption, and incomplete separation of photogenerated carriers of the original material, the photocatalytic performance is poor. In principle, pyridine-2,5-dicarboxylic acid can coordinate with melamine due to its compatibility with the heptazine structure, and pre-generate a supramolecular precursor. The introduction of pyridine-2,5-dicarboxylic acid not only introduces a large amount of π structure, achieving effective combination of π to the original carbon nitride material (PCN), but also allows more carbon atoms to be inserted into the heptazine unit of PCN. The ratio of C element to N element of the carbon nitride photocatalyst before and after modification increases from 0.65 to 0.72, and the two nitrogen atoms in the heptazine structure unit are accurately replaced by the two carbon atoms in the pyridine unit. By changing the mass ratio of the raw materials melamine and pyridine-2,5-dicarboxylic acid to 1:1, 3:1, 5:1, and 10:1, it was found by comparison that the photocatalytic performance of melamine and pyridine-2,5-dicarboxylic acid reached the highest value when the mass ratio was 4:1.

[0032] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0033] (1) The grid-like porous carbon nitride photocatalyst prepared by the method of the present invention utilizes the method of introducing a pyridine group into the heptazine unit of the traditional carbon nitride material, so that the new photocatalyst is improved on the basis of the original photocatalytic performance, and its light absorption range is increased compared with the traditional carbon nitride material, the recombination of photogenerated electrons and holes is reduced, and its photocatalytic oxidation ability is greatly enhanced;

[0034] (2) The present invention uses a preparation method of hydrothermal reaction and thermal polycondensation reaction to prepare a carbon nitride photocatalyst having a grid-like porous structure, which increases the photocatalytic active sites and increases the photocatalytic reaction rate by more than 5 times under the same conditions;

[0035] (3) The grid-like porous carbon nitride photocatalyst of the present invention can achieve photocatalytic oxidation degradation of rhodamine B and photocatalytic oxidation sterilization, and the raw materials for its preparation are cheap and easy to obtain, which is suitable for commercial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and the common carbon nitride photocatalyst;

[0037] Figure 2 Schematic diagram of the preparation process of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1;

[0038] Figure 3 TEM image of the grid-like porous carbon nitride photocatalyst prepared in Example 1;

[0039] Figure 4This is a comparison diagram of the ultraviolet-visible light absorption spectra of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and the common carbon nitride photocatalyst;

[0040] Figure 5 This is an XRD comparison diagram of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and a common carbon nitride photocatalyst;

[0041] Figure 6 FT-IR comparison diagram of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and the common carbon nitride photocatalyst;

[0042] Figure 7 This is a solid NMR comparison diagram of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and a common carbon nitride photocatalyst;

[0043] Figure 8 This is a comparison diagram of the electron paramagnetic resonance of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and the common carbon nitride photocatalyst;

[0044] Fig. 9 It is a comparison diagram of adsorption-desorption curves and specific surface areas of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and the common carbon nitride photocatalyst;

[0045] Fig.10 This is a comparison diagram of the efficiency of the grid-shaped porous carbon nitride photocatalyst and the common carbon nitride photocatalyst in photocatalytic oxidation degradation of Rhodamine B in Example 2;

[0046] Fig.11 This is a diagram of repeated experiments of five times of photocatalytic oxidation degradation of Rhodamine B by grid-like porous carbon nitride in Example 2;

[0047] Fig.12 This is a comparison chart of the efficiency of photocatalytic oxidation killing of Acinetobacter baumannii by the grid-shaped porous carbon nitride photocatalyst and the common carbon nitride photocatalyst in Example 3;

[0048] Fig.13 This is a diagram of repeated experiments in Example 3 in which the grid-shaped porous carbon nitride photocatalytically oxidized five times to kill Acinetobacter baumannii;

[0049] Fig.14 A comparison chart of the photocatalytic sterilization performance of the grid-shaped porous carbon nitride photocatalyst prepared at different thermal polycondensation temperatures;

[0050] Fig.15 This is a comparison chart of the photocatalytic performance of grid-like porous carbon nitride prepared at different feed ratios;

[0051] Fig.16 This is a performance comparison chart of the carbon nitride photocatalyst obtained in Comparative Example 1 and the grid-like porous carbon nitride photocatalyst obtained in Example 1. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0053] Example 1

[0054] (1) 3.20 g of melamine and 0.80 g of pyridine-2,5-dicarboxylic acid were weighed into a 100 mL beaker, 80 mL of 10% acetic acid was added, and the mixture was evenly dispersed by ultrasonication for 30 min. The mixture was then stirred by a magnetic stirring device for 1 h until the solution turned into a milky white colloid. The ultrasonication and stirring temperatures were both 60° C.

[0055] (2) The milky white colloid in step (1) was transferred to a 100 mL polytetrafluoroethylene liner, and the liner was placed in a stainless steel reactor for hydrothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h;

[0056] (3) taking out the liner after the hydrothermal reaction in step (2) is completed, taking out the hydrothermal product in the liner, washing it three times with anhydrous ethanol and deionized water respectively, and then putting the hydrothermal product into a forced air drying oven for drying until the reaction product is completely dry, the drying temperature is 60° C., and the drying time is more than 6 hours;

[0057] (4) placing the completely dried product of step (3) in a crucible, and then placing it in a quartz tube furnace for thermal polycondensation reaction, the thermal polycondensation reaction temperature is 500° C., the thermal polycondensation heating rate is 5° C. / min, the thermal polycondensation reaction time is 6 h, and after the thermal polycondensation reaction is completed, the product in the crucible is taken out and fully ground to obtain a grid-like porous carbon nitride;

[0058] (5) Without any pretreatment, only 3.2 g of melamine was placed in a crucible, which was then placed in a quartz tube furnace and kept at 550 °C for 4 h to prepare ordinary carbon nitride.

[0059] Two samples of the grid-shaped porous carbon nitride and ordinary carbon nitride prepared in this example were placed on weighing paper and photographed for comparison. Figure 1 ; By comparison, it is found that ordinary carbon nitride is a light yellow powder, while the grid-like porous carbon nitride is a light brown powder, and the sample is more fluffy and dense; the preparation process of the grid-like porous carbon nitride is as follows Figure 2 .

[0060] The reason for selecting the acetic acid system is that in the 10% acetic acid system, the white colloid generated by the raw material reaction under the effect of π-π stacking is more dense, and the dense colloid is conducive to the subsequent hydrothermal reaction.

[0061] A small amount of the grid-shaped porous carbon nitride prepared in this example and a common carbon nitride material were dispersed in ethanol respectively. After dispersion, a drop was taken on a copper mesh and dried. Then, the morphology of the two powder samples was observed using a transmission electron microscope. The results are as follows: Figure 3 shown. Figure 3 TEM images of the grid-like porous carbon nitride and ordinary carbon nitride materials prepared in Example 1. Figure 3 It can be seen that the ordinary carbon nitride sheet is thicker, and the grid-like porous carbon nitride has a mesh structure with a large number of holes in the structure.

[0062] A small amount of the grid-shaped porous carbon nitride prepared in this example and ordinary carbon nitride material were placed on the sample stage, and the light absorption performance of the material in the wavelength range of 200nm-800nm ​​was detected using a Cary 5000 UV-Vis-NIR absorption spectrometer UV (Cary 5000). The results are as follows: Figure 4 shown. Figure 4 The solid UV-visible absorption spectra of the grid-like porous carbon nitride prepared in Example 1 and the ordinary carbon nitride material are compared. Figure 4 It can be seen that the absorption range of ordinary carbon nitride is relatively small, and the absorption range is concentrated in 200-450nm. The grid-like porous carbon nitride material shows full-spectrum absorption in the range of 200-800nm, and has the ability to absorb light in the full spectrum range.

[0063] A small amount of the grid-shaped porous carbon nitride prepared in this example and ordinary carbon nitride material were placed on the sample stage, and the XRD images thereof in the range of 5°-80° were detected using a D8 Advance polycrystalline X-ray diffractometer XRD (D8 Advance). The results are as follows: Figure 5 shown. Figure 5 is the XRD comparison diagram of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and the ordinary carbon nitride photocatalyst, Figure 5 It can be seen that the grid-like porous carbon nitride material has a similar XRD pattern to ordinary carbon nitride, proving that the modification has no obvious effect on the crystal form and phase composition of the material.

[0064] 5 mg of the grid-like porous carbon nitride and the common carbon nitride material prepared in this example were mixed and ground with 95 mg of potassium bromide, and then tableted using a tablet press. The infrared absorption spectrum of the material was detected using an Antaris II Fourier transform near-infrared spectrometer (Antains II). The results are as follows: Figure 6 shown. Figure 6 FT-IR comparison diagram of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and the common carbon nitride photocatalyst. Figure 6It can be seen that the grid-like porous carbon nitride material has similar FT-IR graphs to ordinary carbon nitride, proving that the modification has no significant effect on the bonding mode of the material and the functional groups of the material have not changed significantly.

[0065] Take 1g of each of the grid-shaped porous carbon nitride and the common carbon nitride material prepared in this example, and use AVANCE 600 nuclear magnetic resonance spectrometer NMR (AVANCE 600) to test their solid nuclear magnetic spectra. The results are as follows: Figure 7 shown. Figure 7 This is a solid NMR comparison diagram of the grid-like porous carbon nitride photocatalyst prepared in Example 1 and the ordinary carbon nitride photocatalyst. Figure 7 It can be seen that the grid-like porous carbon nitride material has a similar solid NMR image to ordinary carbon nitride, proving that the modification has no significant effect on the heptazine ring structure of the material.

[0066] 2 mg of the grid-like porous carbon nitride prepared in this example and 2 mg of ordinary carbon nitride material were placed in a nuclear magnetic resonance tube, and the EPR spectra of the materials were measured using an A300-10 / 12 paramagnetic resonance spectrometer EPR (A300-10 / 12). The results are as follows: Figure 8 shown. Figure 8 This is a comparison diagram of the electron paramagnetic resonance of the grid-like porous carbon nitride photocatalyst prepared in Example 1 and the ordinary carbon nitride photocatalyst. Figure 8 It can be seen that the peak type of the grid-like porous carbon nitride image is significantly higher, which means that the grid-like porous carbon nitride has a higher ability to separate electron-hole pairs, which is beneficial to the improvement of photocatalytic performance.

[0067] A small amount of the grid-shaped porous carbon nitride prepared in this example and ordinary carbon nitride material were placed on the sample stand, and the adsorption-desorption curve and specific surface area of ​​the material were measured using the Autosorb IQ3 specific surface analysis and pore size comprehensive analyzer BET (Autosorb IQ3). The results are as follows: Fig. 9 shown. Fig. 9 The adsorption-desorption curves and specific surface areas of the grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and the ordinary carbon nitride photocatalyst are compared. Fig. 9 It can be seen that the grid-like porous carbon nitride has a higher desorption-adsorption curve and a huge increase in the specific surface area, which is beneficial for providing more active sites for catalytic reactions and thus improving the photocatalytic performance.

[0068] Example 2

[0069] The grid-shaped porous carbon nitride photocatalyst prepared in Example 1 and a common carbon nitride photocatalyst were used to perform photocatalytic oxidation degradation of the organic pollutant, Rhodamine B.

[0070] A 50 mg / L Rhodamine B solution was prepared to simulate an organic pollutant solution. 50 mL of Rhodamine B solution was taken from each experimental group, and 20 mg of the grid-shaped porous carbon nitride or ordinary carbon nitride material prepared in Example 1 was added to perform a photocatalytic oxidation degradation experiment of organic pollutants. A small amount of reaction solution was taken from the reaction system every 10 min, and the absorbance of the clarified reaction solution was measured by a UV-visible spectrophotometer after filtration to obtain the absorbance value of the solution at 554 nm. The concentration of the reaction solution was calculated from the RhB solution standard curve, and the formula was:

[0071]

[0072] Where DR is the degradation rate of the photocatalyst to the Rhodamine B solution, C0 is the initial concentration of Rhodamine B (mg / L), C t is the concentration of rhodamine B at time t (mg / L).

[0073] The specific operation of photocatalytic oxidation degradation of organic pollutants using the grid-shaped porous carbon nitride prepared in Example 1 and ordinary carbon nitride materials is as follows:

[0074] (1) 50 mg of rhodamine B was dissolved in 1000 mL of deionized water to prepare a 50 mg / L rhodamine B solution to simulate an organic pollutant solution (RhB solution);

[0075] (2) 50 mL of the RhB solution prepared in step (1) was placed in a 100 mL beaker, 20 mg of the grid-like porous carbon nitride prepared in Example 1 was added, and ultrasonic treatment was performed for 30 min to ensure that the material was evenly dispersed in the solution system to obtain a mixed solution;

[0076] (3) The mixed solution of step (2) was placed in a dark environment and stirred for 60 minutes to ensure that the material and RhB reached adsorption-desorption equilibrium. Starting from 0 min under dark conditions, 3 mL of the reaction solution was taken every 10 min, and the absorbance of the clarified reaction solution at 554 nm was measured using a UV-visible spectrophotometer after filtration until the absorbance remained unchanged, i.e., the adsorption-desorption equilibrium state was reached;

[0077] (4) The mixed solution after dark adsorption in step (3) was placed under a xenon lamp light source for a photocatalytic oxidation experiment. The light source power was 300 W and the light intensity was 100 mW / cm -2 Starting from 0 min, 3 mL of the reaction solution was taken every 10 min, filtered, and the absorbance of the clarified reaction solution at 554 nm was measured by a UV-visible spectrophotometer. The reaction was completed when the absorbance of the clarified solution was 0, indicating that the RhB solution had been completely degraded by the photocatalyst. Fig.10 As shown, Fig.10This is a comparison chart of the efficiency of degrading Rhodamine B between the grid-converted porous carbon nitride material and the ordinary carbon nitride material in Example 2. Fig.10 It can be seen that the grid-like porous carbon nitride experimental group has completed the experiment after 30 minutes of reaction, and the RhB solution has been completely degraded with a degradation efficiency of 99.99%, while the ordinary carbon nitride material has not completed the reaction at 90 minutes, and the degradation efficiency in 90 minutes is 81.20%.

[0078] The rate of photocatalytic degradation of Rhodamine B was calculated according to the reaction kinetics simulation formula:

[0079]

[0080] Where C t and C0 is the concentration of the reaction solution at t minutes and the start of the reaction, kapp is the apparent reaction rate constant. The reaction rate constant of the grid-like porous carbon nitride is calculated to be 0.128 min -1 The reaction rate constant of ordinary carbon nitride is 0.025min-1, and the catalytic efficiency is increased by 5.12 times.

[0081] The photocatalytic oxidation degradation experiment performed in Example 2 was repeated five times to ensure that the porous carbon nitride photocatalyst had good reusability. The degradation rate of the photocatalytic oxidation degradation reaction was calculated by the formula:

[0082]

[0083] Calculation is performed, where DR is the degradation rate of the photocatalyst to the Rhodamine B solution, C0 is the initial concentration of Rhodamine B (mg / L), and C t is the concentration of rhodamine B at time t (mg / L), such as Fig.11 As shown, Fig.11 This is a repeated experimental diagram of five times of photocatalytic oxidation degradation of Rhodamine B by the grid-like porous carbon nitride in Example 2. Fig.11 It can be seen that the photocatalytic performance of the grid-like porous carbon nitride is not affected after repeating the experiment five times, which proves that the grid-like porous carbon nitride material prepared by the present invention has good reusability.

[0084] Example 3

[0085] The photocatalytic oxidation sterilization experiment was carried out using the grid-like porous carbon nitride photocatalyst prepared in Example 1 and a common carbon nitride photocatalyst, and the photocatalytic sterilization efficiency of the grid-like porous carbon nitride was determined by killing Acinetobacter baumannii.

[0086] (1) Before the photocatalytic oxidation sterilization experiment began, all experimental equipment was sterilized by high pressure treatment at 121°C for 20 minutes and ultraviolet irradiation for 30 minutes.

[0087] (2) Acinetobacter baumannii is cultured in lysogeny broth (LB) until the logarithmic growth phase, the culture environment is 37°C, and the culture place is a constant temperature incubator. The logarithmic growth phase can be measured by a nucleic acid / protein analyzer. When OD 600 =0.5. Collect 1.0 mL of bacterial solution, centrifuge at 5000 rpm / min for 5 min, and take out the supernatant. Finally, wash three times with 50 mL of standard phosphate buffer (PBS solution), and then disperse in PBS solution. At this time, the concentration of bacterial solution is about 3×10 8 CFU / mL.

[0088] (3) Take the sterilized equipment in step (1) for experiment, add 400 μL of bacterial solution and 20 mg of photocatalyst into a 100 mL beaker, add 20 mL of PBS solution, and sonicate the mixed solution for 30 seconds to ensure that the photocatalyst is evenly dispersed in the solution.

[0089] (4) Place the beaker in step (3) under a xenon lamp to start a photocatalytic oxidation sterilization experiment. The light source power is 300 W and the light intensity is 100 mW / cm -2 A portion of the solution was taken at 0, 20, 40, 60, 80, 100, and 120 minutes, and the experiment was performed using the standard smear method. The bacterial culture dish was placed in a 37°C constant temperature incubator for 12 hours, and then the colony count was performed to calculate the bacterial survival rate. The sterilization rate formula is:

[0090]

[0091] Where SR% is the sterilization rate, C0 is the initial concentration of bacteria at 0 min, C t is the concentration of bacteria at t min. At the same time, equivalent experiments were carried out under dark conditions using photocatalysts and bacterial solutions, and other experimental conditions remained unchanged. In the photocatalytic sterilization experiment, a magnetic stirrer was used to stir the bacterial mixture. In order to avoid temperature changes caused by light, all experiments were carried out in an ice bath. The results are shown in Fig.12 As shown, Fig.12 : is a comparison diagram of the efficiency of photocatalytic oxidation killing of Acinetobacter baumannii by the grid-shaped porous carbon nitride photocatalyst and the ordinary carbon nitride photocatalyst in Example 3; Fig.12 It can be seen that the grid-like porous carbon nitride has a good killing ability against Acinetobacter baumannii, and the sterilization efficiency reaches 99.999% at 120 minutes, while the sterilization efficiency of ordinary carbon nitride under the same conditions is only 83%, far from the standard of complete sterilization.

[0092] The photocatalytic oxidation degradation experiment performed in Example 2 was repeated five times to ensure that the porous carbon nitride photocatalyst had good reusability. The operation in step (4) was repeated five times. The results were as follows: Fig.13 As shown, Fig.13 This is a repeated experimental diagram of the five-time photocatalytic oxidation of the grid-shaped porous carbon nitride to kill Acinetobacter baumannii in Example 3. Fig.13 It can be seen that in the five repeated experiments, the sterilization efficiency of the grid-like porous carbon nitride material was ≥99.999% at 120 min, which ensured the good photocatalytic oxidation sterilization ability of the grid-like porous carbon nitride photocatalyst while ensuring good reusability.

[0093] Example 4

[0094] (1) 3.20 g of melamine and 0.80 g of pyridine-2,5-dicarboxylic acid were weighed into a 100 mL beaker, 80 mL of 10% acetic acid was added, and the mixture was evenly dispersed by ultrasonication for 30 min. The mixture was then stirred by a magnetic stirring device for 1 h until the solution turned into a milky white colloid. The ultrasonication and stirring temperatures were both 60° C.

[0095] (2) The milky white colloid in step (1) was transferred to a 100 mL polytetrafluoroethylene liner, and the liner was placed in a stainless steel reactor for hydrothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h;

[0096] (3) taking out the liner after the hydrothermal reaction in step (2) is completed, taking out the hydrothermal product in the liner, washing it twice with anhydrous ethanol and deionized water respectively, and then putting the hydrothermal product into a forced air drying oven for drying until the reaction product is completely dry, the drying temperature is 60° C., and the drying time is more than 6 hours;

[0097] (4) placing the completely dried product of step (3) in a crucible, and then placing it in a quartz tube furnace for thermal polycondensation reaction, wherein the thermal polycondensation reaction temperature is 550° C., the thermal polycondensation heating rate is 5° C. / min, and the thermal polycondensation reaction time is 6 h. After the thermal polycondensation reaction is completed, the product in the crucible is taken out and fully ground to obtain a grid-like porous carbon nitride; the same process is carried out in parallel at thermal polycondensation reaction temperatures of 470° C., 490° C., 510° C., 520° C., and 530° C. to obtain a grid-like porous carbon nitride.

[0098] According to the steps shown in Example (2), 20 mg of the grid-like porous carbon nitride prepared in Example 1 and Example 4 was taken for photocatalytic sterilization experiment. The experimental results are as follows: Fig.14 As shown, Fig.14 The photocatalytic sterilization performance comparison chart of the grid-like porous carbon nitride photocatalyst prepared at different thermal polycondensation temperatures is shown in Figure 1. Fig.14 It can be seen that with the increase of the thermal polycondensation reaction temperature, the sterilization efficiency of the grid-like porous carbon nitride photocatalyst is best at 490-530°C, and the sterilization efficiency of the photocatalyst prepared at a thermal polycondensation temperature below 490°C or above 530°C is significantly reduced.

[0099] Example 5

[0100] (1) Weigh 3.20 g of melamine and 3.20 g, 1.07 g, 0.64 g, and 0.32 g of pyridine-2,5-dicarboxylic acid in a 100 mL beaker, add 80 mL of 10% acetic acid, and ultrasonicate for 30 min to evenly disperse them. Then, stir them with a magnetic stirring device for 1 h until the raw material changes from a solution to a milky white colloid. The ultrasonication and stirring temperatures are both 60° C.;

[0101] (2) The milky white colloid in step (1) was transferred to a 100 mL polytetrafluoroethylene liner, and the liner was placed in a stainless steel reactor for hydrothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h;

[0102] (3) taking out the liner after the hydrothermal reaction in step (2) is completed, taking out the hydrothermal product in the liner, washing it twice with anhydrous ethanol and deionized water respectively, and then putting the hydrothermal product into a forced air drying oven for drying until the reaction product is completely dry, the drying temperature is 60° C., and the drying time is more than 6 hours;

[0103] (4) placing the completely dried product of step (3) in a crucible, and then placing it in a quartz tube furnace for a thermal polycondensation reaction, wherein the thermal polycondensation reaction temperature is 500° C., the thermal polycondensation heating rate is 5° C. / min, and the thermal polycondensation reaction time is 6 h. After the thermal polycondensation reaction is completed, the product in the crucible is taken out and fully ground to obtain a grid-like porous carbon nitride; according to Example 5, a grid-like porous carbon nitride with a feed ratio of melamine to pyridine-2,5-dicarboxylic acid of 1:1, 3:1, 5:1, and 10:1 is obtained, and the performance is compared with the grid-like porous carbon nitride photocatalyst with a feed ratio of 4:1 obtained in Example 1. The performance comparison is as follows: Fig.15 As shown, Fig.15 The photocatalytic performance comparison diagram of the grid-like porous carbon nitride prepared at different feed ratios, where a is the degradation efficiency diagram of rhodamine B and b is the sterilization efficiency diagram. Fig.15 It can be seen that the grid-like porous carbon nitride prepared with a feed ratio of 4:1 has the best performance, the fastest rate of degradation of rhodamine B, and the highest sterilization efficiency. A feed ratio lower or higher than 4:1 will lead to a significant decrease in the photocatalytic performance of the material.

[0104] Comparative Example 1

[0105] (1) 3.20 g of melamine and 0.21 g of barbituric acid were mixed in 20 mL of deionized water and ultrasonically treated for 4 h. The resulting white precipitate was dried at 60 °C to obtain a melamine-barbituric acid supramolecular precursor.

[0106] (2) The precursor was placed in a 25 mL alumina crucible, and then the 25 mL alumina crucible was placed in a 50 mL crucible, the gap between the two crucibles was filled with aluminum silicate, and then the assembled crucible was placed in a 250 mL crucible, microwave absorber CuO was added, and the assembled crucible was placed in a household microwave oven, and irradiated at a microwave power of 700 W MW for 4 hours to obtain a comparative sample - a carbon nitride photocatalyst prepared by melamine and barbituric acid.

[0107] 20 mg of each of the grid-shaped carbon nitride photocatalyst prepared in Example 1 and the carbon nitride photocatalyst prepared by melamine and barbituric acid in Comparative Example 1 were used for a photocatalytic performance comparison experiment. Fig.16 As shown, Fig.16 The performance comparison diagram of the carbon nitride photocatalyst obtained in Comparative Example 1 and the grid-shaped porous carbon nitride photocatalyst obtained in Example 1 is shown in Figure 1, wherein a is the efficiency diagram for degradation of rhodamine B, and b is the schematic diagram for sterilization efficiency. Fig.16 It can be seen that the grid-like porous carbon nitride photocatalyst prepared by the method of Example 1 of the present invention has better performance, and the efficiency of degradation of Rhodamine B and photocatalytic sterilization experiments are far higher than that of Comparative Example 1.

[0108] Meanwhile, the yields of the photocatalysts prepared in Example 1, Example 4 and Comparative Example 1 are statistically shown in Table 1.

[0109] Table 1

[0110] raw material Reaction temperature Raw material quality Generated products Yield Melamine, pyridine-2,5-dicarboxylic acid 470℃ 4.0g 3.17g 79.25% Melamine, pyridine-2,5-dicarboxylic acid 490℃ 4.0g 2.98g 74.50% Melamine, pyridine-2,5-dicarboxylic acid 500℃ 4.0g 3.05g 76.25% Melamine, pyridine-2,5-dicarboxylic acid 510℃ 4.0g 2.63g 65.75% Melamine, pyridine-2,5-dicarboxylic acid 520℃ 4.0g 2.26g 56.50% Melamine, pyridine-2,5-dicarboxylic acid 530℃ 4.0g 1.35g 33.75% Melamine, pyridine-2,5-dicarboxylic acid 550℃ 4.0g 0.61g 15.25% Melamine, barbituric acid 550℃ 4.0g 0.42g 10.5%

[0111] It can be seen from Table 1 that, under the same raw material conditions, the yield of the product produced by the method of the present invention is much higher than the yield of the product in Comparative Example 1. At the same time, it can be seen that the thermal polycondensation temperature of the method of the present invention has a greater impact on the product. When the temperature is lower than 490°C, that is, when the thermal polycondensation reaction starts at 470°C, the yield of the thermal polycondensation reaction is higher but the photocatalytic performance is not good. The reason is that the temperature at which the thermal polycondensation reaction of the precursor begins is not reached, and a large amount of precursor remains unreacted. When the temperature exceeds 530°C, that is, reaches 550°C, the yield drops sharply and the photocatalytic performance of the product drops significantly. The reason is that the temperature of the thermal polycondensation reaction is too high, which destroys the structure of carbon nitride. Therefore, within the range of the present application, the yield is better within 490-530°C.

Claims

1. An application of a grid-like porous carbon nitride photocatalyst in photocatalytic oxidation degradation of organic pollutant Rhodamine B or photocatalytic oxidation killing of bacteria, characterized in that: The preparation method of the grid-shaped porous carbon nitride photocatalyst comprises the following steps: (1) adding melamine and pyridine-2,5-dicarboxylic acid to an acetic acid solution, ultrasonicating, stirring and mixing, and obtaining a milky white colloid through π-π stacking, wherein the mass ratio of melamine to pyridine-2,5-dicarboxylic acid is 4:1, the concentration of the acetic acid solution is 10%, and the temperature of ultrasonication and stirring is 50-60°C; (2) placing the milky white colloid in a reaction kettle and performing a hydrothermal reaction to obtain a reaction product, wherein the hydrothermal reaction time is 18-24 hours and the hydrothermal reaction temperature is 160-200° C.; (3) The reaction product is washed, dried, placed in a quartz tube furnace for thermal polycondensation reaction, and ground to obtain the target grid-like porous carbon nitride photocatalyst. The temperature of the thermal polycondensation reaction is 500° C., the time of the thermal polycondensation reaction is 6 hours, and the thermal polycondensation reaction is carried out in an air atmosphere throughout the process.

Citation Information

Patent Citations

  • Polymer photocatalyst as well as preparation method and application thereof

    CN103638960A

  • Porous molecule doped carbon nitride photocatalyst and preparation method and application thereof

    CN109351362A

  • Doped graphitic carbon nitrides, methods of making and uses of the same

    US20170232427A1